Encyclopedia of aesthetics - Kelly, Michael, 1953- (New York : Oxford University Press, 1998)
"Are things ugly or are they just not beautiful? The answer to this and many other questions can be found in this encyclopedia, the first large-scale comprehensive English-language reference on aesthetics and destined to be a classic in the field. Drawing from experts in the areas of philosophy, art, history, psychology, feminist theory, legal theory, and many more, the encyclopedia presents 600 signed essays alphabetically arranged. Most entries include a headnote clarifying the topic. Entries range from the philosophical essay on ugliness, to the more reality-based article on the impact of AIDS on the arts. Comprehensive coverage includes key figures, concepts, periods, theories, and movements in the history of aesthetics."--"Outstanding Reference Sources: the 1999 Selection of New Titles", American Libraries, May 1999. Comp. by the Reference Sources Committee, RUSA, ALA.
Includes bibliographical references and index.
Keywords: Aesthetics -- Encyclopedias